If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4r + 7 = 43 Reorder the terms: 7 + 4r = 43 Solving 7 + 4r = 43 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4r = 43 + -7 Combine like terms: 7 + -7 = 0 0 + 4r = 43 + -7 4r = 43 + -7 Combine like terms: 43 + -7 = 36 4r = 36 Divide each side by '4'. r = 9 Simplifying r = 9
| 4(x-3)(x-3)=1 | | -10x^2+2=292 | | 3x+12/4x+16 | | 3x+1/5y=7 | | 1x+2x=9 | | -3=r/-42 | | h/2+6=9 | | 3g+14=13 | | 4/5*20 | | 8=8w-4(w+8) | | -16-6r=-2(8v-7) | | (1x-3)(x-3)=1 | | 13=x/-4 | | 1/3x+y=4 | | (3x-1)(2x+2)=12 | | 9x-24=7x+18 | | log(5x-1)=2 | | 4(x+7)=2(3x-2) | | 75y^2-30y+3=0 | | 3x^2-8=19 | | 3=y/16 | | 9x-24=x+18 | | x^2-cx-16=0 | | 4=-2(1/2-1) | | 10=b(0.6) | | 10=b | | -18=y/-2 | | 8(2c+2v-9d)= | | 3x^2-36x+96=0 | | (2x^2-13x+15)/(x^2-25) | | 54=-16t^2+70t | | -7n+28=4(7+7n) |